2020
DOI: 10.3389/fgene.2019.01397
|View full text |Cite
|
Sign up to set email alerts
|

MiR-199b-5p Suppresses Tumor Angiogenesis Mediated by Vascular Endothelial Cells in Breast Cancer by Targeting ALK1

Abstract: Angiogenesis is a crucial event during cancer progression that regulates tumor growth and metastasis. Activin receptor-like kinase 1 (ALK1), predominantly expressed in endothelial cells, plays a key role in the organization of neo-angiogenic vessels. Therapeutic targeting of ALK1 has been proposed as a promising strategy for cancer treatment, and microRNAs (miRNAs) are increasingly being explored as modulators of angiogenesis. However, the regulation of ALK1 by miRNAs is unclear. In this study, we identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Additionally, miR-199b-5p-overexpression inhibited the mRNA and protein expression of activin receptor-like kinase 1, and the formation of capillary-like tubular structures in HUVECs. Furthermore, it attenuated the induction of the activin receptor-like kinase 1/Smad/Id1 pathway in HUVECs (73). These findings further establish the involvement of these miRNAs in breast cancer metastasis and their potential as future breast cancer biomarkers.…”
Section: Lung Cancersupporting
confidence: 60%
“…Additionally, miR-199b-5p-overexpression inhibited the mRNA and protein expression of activin receptor-like kinase 1, and the formation of capillary-like tubular structures in HUVECs. Furthermore, it attenuated the induction of the activin receptor-like kinase 1/Smad/Id1 pathway in HUVECs (73). These findings further establish the involvement of these miRNAs in breast cancer metastasis and their potential as future breast cancer biomarkers.…”
Section: Lung Cancersupporting
confidence: 60%
“…Angiogenesis is the central marker of tumors and is key for the progression and metastasis of solid tumors ( 6 ). HUVECs are a classic model system to study angiogenesis ( 29 ). Previous studies have demonstrated that tumor cells can improve the proliferation and migration of VECs, and promote angiogenesis to a certain extent ( 30 – 32 ); activated PLTs are also involved in this process ( 16 , 17 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Study has found that miR-199b-5p is highly expressed in osteosarcoma and promotes the malignant development of osteosarcoma ( 10 ). However, miR-199b-5p is under-expressed in prostate cancer and breast cancer and inhibits tumor cell growth ( 11 , 12 ). These studies show that miR-199b-5p plays a two-way regulatory role in different cancer cells.…”
Section: Introductionmentioning
confidence: 99%